Answer:
The 13th term is 81<em>x</em> + 59.
Step-by-step explanation:
We are given the arithmetic sequence:
![\displaystle -3x -1, \, 4x +4, \, 11x + 9 \dots](https://tex.z-dn.net/?f=%5Cdisplaystle%20-3x%20-1%2C%20%5C%2C%204x%20%2B4%2C%20%5C%2C%2011x%20%20%2B%209%20%5Cdots)
And we want to find the 13th term.
Recall that for an arithmetic sequence, each subsequent term only differ by a common difference <em>d</em>. In other words:
![\displaystyle \underbrace{-3x - 1}_{x_1} + d = \underbrace{4x + 4} _ {x_2}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cunderbrace%7B-3x%20-%201%7D_%7Bx_1%7D%20%2B%20d%20%3D%20%5Cunderbrace%7B4x%20%2B%204%7D%20_%20%7Bx_2%7D)
Find the common difference by subtracting the first term from the second:
![d = (4x+4) - (-3x - 1)](https://tex.z-dn.net/?f=d%20%3D%20%284x%2B4%29%20-%20%28-3x%20-%201%29)
Distribute:
![d = (4x + 4) + (3x + 1)](https://tex.z-dn.net/?f=d%20%3D%20%284x%20%2B%204%29%20%2B%20%283x%20%2B%201%29)
Combine like terms. Hence:
![d = 7x + 5](https://tex.z-dn.net/?f=d%20%3D%207x%20%2B%205)
The common difference is (7<em>x</em> + 5).
To find the 13th term, we can write a direct formula. The direct formula for an arithmetic sequence has the form:
![\displaystyle x_n = a + d(n-1)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x_n%20%3D%20a%20%2B%20d%28n-1%29)
Where <em>a</em> is the initial term and <em>d</em> is the common difference.
The initial term is (-3<em>x</em> - 1) and the common difference is (7<em>x</em> + 5). Hence:
![\displaystyle x_n = (-3x - 1) + (7x+5)(n-1)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x_n%20%3D%20%28-3x%20-%201%29%20%2B%20%287x%2B5%29%28n-1%29)
To find the 13th term, let <em>n</em> = 13. Hence:
![\displaystyle x_{13} = (-3x - 1) + (7x + 5)((13)-1)](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x_%7B13%7D%20%3D%20%28-3x%20-%201%29%20%2B%20%287x%20%2B%205%29%28%2813%29-1%29)
Simplify:
![\displaystyle \begin{aligned}x_{13} &= (-3x-1) + (7x+5)(12) \\ &= (-3x - 1) +(84x + 60) \\ &= 81x + 59 \end{aligned}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Cbegin%7Baligned%7Dx_%7B13%7D%20%26%3D%20%28-3x-1%29%20%2B%20%287x%2B5%29%2812%29%20%5C%5C%20%26%3D%20%28-3x%20-%201%29%20%2B%2884x%20%2B%2060%29%20%5C%5C%20%26%3D%2081x%20%2B%2059%20%5Cend%7Baligned%7D)
The 13th term is 81<em>x</em> + 59.
Answer:
100%
Step-by-step explanation:
Start with x.
x = x/1
Increase the numerator by 60% to 1.6x.
Decrease the numerator by 20% to 0.8.
The new fraction is
1.6x/0.8
Do the division.
1.6x/0.8 = 2x
The fraction increased from x to 2x. It became double of what it was. From x to 2x, the increase is x. Since x was the original number x is 100%.
The increase is 100%.
Answer:
Angle 1 = 85*
Angle 3 = 85*
Angle 4 = 95*
Angle 5 = 85*
Angle 6 = 95*
Angle 7 = 85*
Angle 8 = 95*
Step-by-step explanation:
Since angle 2 is 95*, angle 4 would be the exact same. Now you add 95+95=190 and subtract that from 360. 360-190=170. Then divide 170 by 2= 85 to get the measurements for 1 and 3.
A. False
Why? Because you cut off the triangle. The measurements are 20 mm and 10 mm.
B. True
Why? Because 20*10 = 200
C. False
Why? Because the base is 6 since 26 - 20 is 6. The height is 4, not 6 because 10 - 6 is 4.
D. True
Why? Because like question C., the base is 6, and the height is 4. 6*4 is 24/2 = 12. If you don't get this, the formula for all triangles is b*h*1/2
E. True
Why? Because from questions B. and D., the area of the rectangle is 200 and the area of the triangle is 12. 200 + 12 = 210.
Hope this helped,
Loafly